2020
DOI: 10.1177/0194599820971186
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Practice Providers Utilization Trends in Otolaryngology From 2012 to 2017 in the Medicare Population

Abstract: Objective Nurse practitioners and physician assistants form a growing advanced practice provider (APP) group. We aim to analyze the trends and types of services provided by APPs in otolaryngology. Study Design Cross-sectional study. Setting Medicare Provider Utilization and Payment Data: Physician and Other Supplier Public Use Files, 2012-2017. Methods The Medicare database was searched for 13 commonly used otolaryngology-specific Current Procedural Terminology ( CPT) codes, and 10 evaluation and management (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 16 publications
2
40
0
Order By: Relevance
“…28 Given the recent increase in the prevalence of advanced practice providers in otolaryngology practices, particularly nurse practitioners and physician assistants, the trend in consolidation of services may be even more pronounced than what our study suggests, as the overall volume of care being delivered per site is consolidated. 29,30 Last, it is important to note that our results and analysis compare the trends of size of practice, and in this way, we are unable to conclude anything on the trends relating to private vs academic practices. While many small practices are private ventures, further research is needed to assess whether these changes are being similarly seen with regard to private practice consolidation.…”
Section: Discussionmentioning
confidence: 84%
“…28 Given the recent increase in the prevalence of advanced practice providers in otolaryngology practices, particularly nurse practitioners and physician assistants, the trend in consolidation of services may be even more pronounced than what our study suggests, as the overall volume of care being delivered per site is consolidated. 29,30 Last, it is important to note that our results and analysis compare the trends of size of practice, and in this way, we are unable to conclude anything on the trends relating to private vs academic practices. While many small practices are private ventures, further research is needed to assess whether these changes are being similarly seen with regard to private practice consolidation.…”
Section: Discussionmentioning
confidence: 84%
“…8 Given the increasing role of APPs in otolaryngology and the increased likelihood of APPs to practice in rural communities, understanding the geographic distribution of APPs providing otolaryngology services is necessary to address future shortages. 15…”
Section: Discussionmentioning
confidence: 99%
“…10-12 APPs are also playing a rapidly growing role within otolaryngology, increasing by 51% in number from 2012 to 2017, as compared with just 2.2% growth in otolaryngology physicians over the same period. 13-15 APPs can independently provide otolaryngologic services and bill Medicare under their own National Provider Identifiers, and NPs can practice with full independence in 22 states and the District of Columbia. 16 This study analyzes the geographic distribution of APPs independently billing Medicare for otolaryngology services with a focus on urban-rural disparities.…”
mentioning
confidence: 99%
“…2 The present study found that advanced practice providers had fewer reviews than did physicians. In one study of Medicare data for years 2012-2017, there was no difference over time in number of patient visits performed annually per provider according to provider type, 28 but another study found that otolaryngology physicians provided more services and higher median number of Medicare patients than did advanced practice providers. 29 We speculate that the explanation for the difference in volume of PSS between advanced practice providers and The present study also found there are fewer women providers in academic otolaryngology, but women and men had similar overall and subgroup PSS.…”
Section: Discussionmentioning
confidence: 99%